(untitled) (Vietnam Journal of Community Medicine, 2026)
A cross-sectional study on 541 grade 9 students, junior high school in Hanoi city from March 1, 2024 to May 30, 2024. Objective: The study aims to determine the rate and some factors related to signs of anxiety in senior high school students in Hanoi city. Results: 49.72% of students have signs of anxiety at different levels: mild level is 25.69%, moderate level is 10.54%, severe level is 13.49%. Factors that are statistically significant with the rate of students with signs of anxiety are: Gender, academic pressure, physical bullying, phone addiction (p<0.01). Conclusion: 49.72% of senior high school students in Hanoi city have signs of anxiety at different levels. Solutions should focus on factors such as academic pressure, physical bullying, and phone addiction in students.